Findbuch des Bestandes Abt. 320.6. Kreis Flensburg-Land 1867-1968 - Haase, Hartmut (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2017)
The county of Flensburg-Land was founded by the Prussian decree of September 22, 1867. Initially, the former Office Flensburg with its properties, the city of Flensburg, the small town of Glücksburg, the First Anglian Property District ("Erster Angler Güterdistrik") as well as the 'enclaved' county places belonging to the Monastery of St. Johannis belonged to the newly founded county. By the county order of May 26, 1888, the city of Flensburg separated from the district and from then on formed the city of Flensburg with an own county status. Between 1920 and 1944 the stock of the archival material was handed over to the Regional archives of Kiel. Because of the war-related outsourcing, there were only insignificant losses. In 1966 the stock was inspected, rearranged and listed. It was only in 2007 that a further archival exchange with the district archives of Schleswig-Flensburg extended the inventory by a further 150 distribu- tion units. At the same time, the files of the Flensburger Kreisbahn which had previously been kept as separate stock were renumbered and integratd into the main stock in the old order.